Analisis Sistematis tentang Resesi Ekonomi: Penyebab, Dampak dan Strategi Menghadapinya melalui Tinjauan Literatur - Asri Meilandari (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This research aims to systematically analyze the causes, impacts, and strategies for addressing economic recessions through the Systematic Literature Review (SLR) method. Using the PRISMA guidelines, this study identifies and synthesizes scientific literature from 2020 to 2025 that discusses economic recessions in both global and national contexts. The study results show that the economic recession is triggered by various factors such as high inflation, energy crises, global pandemics, and geopolitical tensions. The impact extends to the labor sector, the business world, and the social conditions of society, particularly on MSMEs and vulnerable groups. Effective strategies for facing a recession include coordinated fiscal and monetary policies, strengthening the domestic economy, as well as technology-based innovation and multisector collaboration. These findings provide a conceptual foundation for formulating adaptive economic policies in facing future economic crises.